Pixualization: Glitch art and Data visualization - Peña, Ernesto; Dobson, Teresa M.; Juárez, Omar (InfoDesign, 2017)
Due to their trans-modal affordances, techniques mainly used for the production of glitch art such as pixel sorting and data-bending are potential data visualization tools that can be effectively adapted to the representation of abstract relations. To demonstrate this assertion, we present a method intended for the visualization of data through these techniques. The method presented here consists in sorting the composite pixels of greyscale images to make evident relationships between pixels that otherwise would be impossible to perceive. Here, we use this method to arrange an array of images in a very specific order, but this is only one of the potential applications that this method could have.